Development and Validation of an Open-Source Reservoir Simulator: A Comparative Study with Commercial Software - Amrajaa Ahmed salih handar (Surman Journal of Science and Technology, 2025)
Reservoir simulation is a critical tool for predicting hydrocarbon recovery and optimizing field development strategies. While commercial software packages like Schlumberger's ECLIPSE are industry standards, their high cost and closed-source nature limit accessibility and customization, particularly in academia. This study investigates the potential of open-source software as a viable alternative for reservoir simulation. We developed a specialized single-phase reservoir solver, PRS Foam, within the open-source Computational Fluid Dynamics (CFD) platform OpenFOAM. The solver implements a simplified black-oil model for incompressible fluid flow through a compressible porous medium. To validate its accuracy, we conducted a comprehensive comparative analysis against the commercial simulator ECLIPSE. Three test cases of varying complexity were designed: a simple homogeneous "shoe-box" model (TESTCASE_1), a complex, geologically realistic model (TESTCASE_2), and a single-phase injection-production scenario (WATER_INJECTION). Results demonstrated a remarkable agreement between PRSFoam and ECLIPSE. For the simple model, pressure and production rate discrepancies were less than 1.5% over four years. Even for the complex model, the differences in cumulative production after 20 years were only 3.24%, and pressure distributions were visually and quantitatively consistent. This work confirms that open-source-based reservoir simulation, leveraging tools like OpenFOAM, can achieve a high degree of accuracy comparable to established commercial software. It presents a cost-effective, flexible, and pedagogically valuable platform for academic research and training, with significant potential for future development towards more complex, multi-phase flow simulations.